2008
DOI: 10.1103/physrevb.77.195431
|View full text |Cite
|
Sign up to set email alerts
|

Helium in polygonal nanopores at zero temperature: Density functional theory calculations

Abstract: We investigate adsorption of helium in nanoscopic polygonal pores at zero temperature using a finite-range density functional theory. The adsorption potential is computed by means of a technique denoted as the elementary source method. We analyze a rhombic pore with Cs walls, where we show the existence of multiple interfacial configurations at some linear densities, which correspond to metastable states. Shape transitions and hysterectic loops appear in patterns which are richer and more complex than in a cyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…[12]. In particular, Cs substrates of diverse shapes are excellent candidates to investigate nontrivial aspects of the physics of wetting, since the soft He-Cs potential, that prevents helium from condensing into a thick film on planar Cs surfaces at zero temperature, can be substantially enhanced by curving or folding the plane, giving rise, for example, to filling of linear wedges of intermediate openings [9], of infinite pores with polygonal section [10] as well as cavities on a nanostructured surface [5,11]. One additional advantage of carrying FRDF calculations with alkali metal surfaces is the substantial reduction in computing time with respect to the very strong graphite substrate, yielding results which are qualitative akin to those expected for very large adsorption strengths.…”
Section: Introductionmentioning
confidence: 99%
“…[12]. In particular, Cs substrates of diverse shapes are excellent candidates to investigate nontrivial aspects of the physics of wetting, since the soft He-Cs potential, that prevents helium from condensing into a thick film on planar Cs surfaces at zero temperature, can be substantially enhanced by curving or folding the plane, giving rise, for example, to filling of linear wedges of intermediate openings [9], of infinite pores with polygonal section [10] as well as cavities on a nanostructured surface [5,11]. One additional advantage of carrying FRDF calculations with alkali metal surfaces is the substantial reduction in computing time with respect to the very strong graphite substrate, yielding results which are qualitative akin to those expected for very large adsorption strengths.…”
Section: Introductionmentioning
confidence: 99%
“…In cases where the physical effects of such structure can be safely neglected, as for alkali-metal surfaces interacting with liquid helium, it provides a good adsorption potential for nonplanar geometries. 22 We have considered an alkali planar surface hosting a periodic array of parabolic nanocavities of height h =35 Å and outer radius R = 25 Å lying on the ͑x , y͒ plane. This geometry is inspired on substrates studied in Ref.…”
Section: Theory and Numerical Proceduresmentioning
confidence: 99%
“…14 More recently, the existence of natural and manufactured nanopores 15,16 on the one side, and, on the other, the possibility of growing surfaces structured within the nanoscale, triggered experimental and theoretical lines of research, oriented toward pore filling and wetting of nanopatterned substrates by classical fluids. [16][17][18] The condensation of helium in nanopores at zero temperature has been analyzed using variational Jastrow-Feenberg, 19 variational Monte Carlo, 20 and mean field 21,22 techniques; in particular, we have proven that finite-range density-functional ͑FRDF͒ theory is a powerful instrument in detecting multiple equilibrium states and trace hysteretic loops in the road toward capillary condensation of helium in weakly adsorbing pores. 22 On the other hand, finite temperature FRDF is also adequate in examining aspects of wetting properties of helium on Cs, such as the contact angle 23,24 and the wetting temperature of the semi-infinite metal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, it has been shown that in addition to the well-known filling transition, which occurs as the liquidvapor interface becomes flat, an "emptying" transition preannouncing the formation of a bridge can take place for sufficiently narrow openings. Furthermore, the study of the adsorbed density profiles and their energetics has provided a reference frame for more involved analysis of the adsorption isotherms of helium in infinite pores 15 and on nanostructured surfaces. 16 Since these studies concentrate on the equilibrium properties of the confined fluid, it is natural to take one step forward and interrogate oneself about the low-energy collective excitations supported by such systems.…”
Section: Introductionmentioning
confidence: 99%